Laboratory indicators of the disorders of immune-endocrine balance in children with acute respiratory viral infection during post-COVID period - L. A. Alekseeva; A. A. Zhirkov; T. V. Bessonova; I. V. Babachenko; N. S. Tian; G. F. Zheleznikova (Журнал инфектологии)
Objective of the study is to investigate immune-endocrine dysfunctions in children with acute respiratory viral infections manifested during post-COVID period.Materials and methods. The main group included 22 children with acute respiratory viral infections manifested after mild COVID-19 infection 2–6 months before their hospitalization the comparison group included 7 children with acute respiratory viral infections without COVID-19 in their medical history; and the control group – 15 apparently healthy children. The level of cortisol; thyrotrophic hormone; triidothyronine; thyroxin; total immunoglobulin; cytokines was investigated in addition to standard indicators.Results. Lymphocytes predominated in the blood test in the main group at the admission to the hospital; whereas neutrophils predominated in children of the comparison group. In comparison with the controls the children of the main group had significant decrease of the level of 25 cytokines and the level of only 4 cytokines was increased (CTACK; Eotaxin; SDF-1a; PDGF-BB); the tendency of immunoglobulin M decrease was noted. The level of cortisol in the main group was 2 times lower compared with the comparison group and did not differ from the control one; the level of triidothyronine and thyroxin was reliably decreased during the whole period of observation. During acute period there was determined positive correlated relation of cortisol with the number of neutrophils; granulocytic colony-stimulating factor; macrophage inflammatory protein; and a negative relation with the number of lymphocytes; factor-stromal cells. During acute period there were positive correlated relations between the level of triidothyronine and the number of platelets; immunoglobulin M; and during reconvalescence period the level of triidothyronine and thyroxin positively correlated with the number of neutrophils; and negatively with the number of lymphocytes.Conclusion. During post-COVID period children after acute respiratory viral infections had identified immuneendocrine dysfunctions giving evidence to inhibition of the synthesis of hormones of adrenal gland cortex and thyroid system; synthesis of most cytokines; insufficient activation of congenital immunity that is likely to occur due to COVID-19 that proves the necessity of immune-corrective therapy.